The courts and the code. Legal osmosis between religion and law in the cultural framework of civil law systems (Stato, Chiese e pluralismo confessionale, 2017)
SUMMARY: 1. The value of religious law in modern (and secular) states - 2. Religious rules and individual choices in Europe - 3. Religious law and the fields in which it can operate effectively - 4. The rules of religious courts in civil legal systems - 4.1 ..The direct referral to religious laws - 4.2. The pronounces of religious courts and its importance for faithful - 5. The development of Religious Arbitration Courts in Italy - 6. Does religious jurisdiction another side of religious freedom?